A Study of NCAA Gambling Prevention Videos on Gambling Perceptions Within a NCAA Division II Baseball Team - Timothy Mowrer; Jeffrey W. Wimer; Rebecca J. Mowrey; Daniel F. O'Neill (University of Kansas Libraries, 2016)
The purpose of this study was to investigate gambling attitudes among collegiate baseball players. We wanted to know if online educational videos developed by the NCAA would be successful in altering gambling attitudes and behaviors. A Randomized Controlled Trial (RCT) with a pretest-posttest design was conducted for this study. Subjects included a convenience sample of 33 baseball studentathletes from a NCAA Division II University in the mid-Atlantic region. Gambling attitudes and behaviors of collegiate baseball student-athletes were determined through survey questions and the administration of the South Oaks Gambling Screen. Findings indicated that baseball student-athletes participated in a variety of gambling activities, and that NCAA educational videos are moderately successful in altering student-athletes' attitudes toward gambling. This study is important for college and university athletics departments as they work to counter the progambling messages that student-athletes receive.